Wiley CPAexcel exam review 2015 focus notes : auditing and attestation. (John Wiley & Sons, 2015)
All the information you need to pass the CPA exam on your own Updated annually with the latest AICPA content guidelines, Wiley CPaexcel Exam Review 2015 Focus Notes provides a review of all the basic skills and concepts tested on the CPA exam and teaches important strategies to take the exam faster and more accurately. Filled with acronyms and mnemonic devices to help candidates remember the accounting rules and checklists needed to pass the exam, Wiley CPaexcel Exam Review 2015 Focus Notes provides a thorough review of all basic skills and concepts needed for the exam.-Includes tips on identifying and interpreting annual reports, stock reports, and other published material to help with the research requirements of the new case study simulations -Available in a handy, easy-to-carry, spiral bound reference manual -Includes acronyms and mnemonics to help candidates learn and remember a variety of rules and checklists In order to assist candidates in successfully performing exam simulations, Wiley CPaexcel Exam Review 2015 Focus Notes include references to authoritative literature, sample spreadsheets, and key concepts, tips and tools to facilitate research.